Le stage comme dispositif de transfert des compétences professionnelles d’enseignants haïtiens en formation initiale - Marie-Rose Magaly Guervil; Claire Duchesne (Éducation et Socialisation)
This article reports the results of research into the transfer of skills during teacher training practica in Haiti. Ten students participated in semi-structured interviews, reporting on how they were able to transfer skills developed from facing challenges during their practica. In addition to describing the contribution of their practica to their professional training, the article discusses ideas for amending teacher practica supervision and to maximize the potential for reflective practice.